Theileria equi claudin like apicomplexan microneme protein contains neutralization-sensitive epitopes and interacts with components of the equine erythrocyte membrane skeleton - Onzere, Cynthia K. (Sci Rep, 2021)
Theileria equi is a widely distributed apicomplexan parasite that causes severe hemolytic anemia in equid species. There is currently no effective vaccine for control of the parasite and understanding the mechanism that T. equi utilizes to invade host cells may be crucial for vaccine development. Unlike most apicomplexan species studied to date, the role of micronemes in T. equi invasion of host cells is unknown. We therefore assessed the role of the T. equi claudin-like apicomplexan microneme protein (CLAMP) in the invasion of equine erythrocytes as a first step towards understanding the role of this organelle in the parasite. Our findings show that CLAMP is expressed in the merozoite and intra-erythrocytic developmental stages of T. equi and in vitro neutralization experiments suggest that the protein is involved in erythrocyte invasion. Proteomic analyses indicate that CLAMP interacts with the equine erythrocyte α-and β- spectrin chains in the initial stages of T. equi invasion and maintains these interactions while also associating with the anion-exchange protein, tropomyosin 3, band 4.1 and cytoplasmic actin 1 after invasion. Additionally, serological analyses show that T. equi-infected horses mount robust antibody responses against CLAMP indicating that the protein is immunogenic and therefore represents a potential vaccine candidate.